2012
DOI: 10.1007/s11357-012-9468-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nicotinic acetylcholine receptor turnover by MuRF1 connects muscle activity to endo/lysosomal and atrophy pathways

Abstract: Muscle atrophy is a process of muscle wasting induced under a series of catabolic stress conditions, such as denervation, disuse, cancer cachexia, heart and renal failure, AIDS, and aging. Neuromuscular junctions (NMJs), the synapses between motor neurons and muscle fibers undergo major changes in atrophying muscles, ranging from mild morphological alterations to complete disintegration. In this study, we hypothesized that remodeling of NMJs and muscle atrophy could be linked together. To test this, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 61 publications
0
73
0
Order By: Relevance
“…44 We have recently shown that endogenous TRIM63 is highly enriched at the nerve-muscle synapse, the neuromuscular junction, and heterologous expression of TRIM63-GFP is detected by in vivo microscopy in puncta colocalizing with internalized CHRN, the major postsynaptic ion channel of the NMJ. 28 Furthermore, since CHRN half-life upon denervation is significantly stabilized in trim63 −/ − mice and TRIM63 coprecipitates with CHRN, a crucial role of TRIM63 for CHRN turnover was claimed. 28 Despite the enormous physiological relevance of CHRN, deplorably little is known about the mechanisms driving its turnover.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…44 We have recently shown that endogenous TRIM63 is highly enriched at the nerve-muscle synapse, the neuromuscular junction, and heterologous expression of TRIM63-GFP is detected by in vivo microscopy in puncta colocalizing with internalized CHRN, the major postsynaptic ion channel of the NMJ. 28 Furthermore, since CHRN half-life upon denervation is significantly stabilized in trim63 −/ − mice and TRIM63 coprecipitates with CHRN, a crucial role of TRIM63 for CHRN turnover was claimed. 28 Despite the enormous physiological relevance of CHRN, deplorably little is known about the mechanisms driving its turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous extensive work on the mechanisms underlying CHRN recycling 25,34,35 and CHRN degradation identified an interaction between CHRN and the E3 ligase TRIM63. 28 Furthermore, the previously reported direct interaction between TRIM63 and SQSTM1 29 prompted us to speculate that TRIM63 may induce selective autophagy as a principal route for CHRN removal. To address this issue, we first transfected the autophagic marker GFP-MAP1LC3A into live mouse muscle.…”
Section: Starvation Destabilizes Chrnmentioning
confidence: 94%
See 3 more Smart Citations